2018
DOI: 10.1038/s41467-018-04479-z
|View full text |Cite
|
Sign up to set email alerts
|

Crystal step edges can trap electrons on the surfaces of n-type organic semiconductors

Abstract: Understanding relationships between microstructure and electrical transport is an important goal for the materials science of organic semiconductors. Combining high-resolution surface potential mapping by scanning Kelvin probe microscopy (SKPM) with systematic field effect transport measurements, we show that step edges can trap electrons on the surfaces of single crystal organic semiconductors. n-type organic semiconductor crystals exhibiting positive step edge surface potentials display threshold voltages th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 46 publications
5
71
1
Order By: Relevance
“…This interface is free of polaronic effects and strain, but it is not exempt from the trapping resulting from imperfections at the crystal surface. Crystal step edges present on the surfaces of organic semiconductors single crystal were found to be trapping sites for the charges accumulated at the interface between the crystal and the dielectric . While we do not have a quantitative analysis of the density of the step edges in our crystals, by simple optical inspection it can be clearly seen that their density is very high.…”
Section: Resultsmentioning
confidence: 99%
“…This interface is free of polaronic effects and strain, but it is not exempt from the trapping resulting from imperfections at the crystal surface. Crystal step edges present on the surfaces of organic semiconductors single crystal were found to be trapping sites for the charges accumulated at the interface between the crystal and the dielectric . While we do not have a quantitative analysis of the density of the step edges in our crystals, by simple optical inspection it can be clearly seen that their density is very high.…”
Section: Resultsmentioning
confidence: 99%
“…d) Energy level diagram of Cl 2 ‐NDI including the energy state of step edges. Reproduced with permission . Copyright 2018, Springer Nature.…”
Section: Experimental Methods For Investigating Charge Trapsmentioning
confidence: 99%
“…He et al directly visualized the trap states present at structural defects (i.e., at a crystal edge) on the surface of an n‐type semiconductor by using SKPM . The authors investigated in detail the correlation between field‐effect charge transport and structural properties (the density of the crystal step edge and the crystal orientation) of a single crystal of N , N ′‐bis‐(heptafluorobutyl)‐2,6‐dichloro‐1,4,5,8‐naphthalene tetracarboxylic diimide (Cl 2 ‐NDI).…”
Section: Experimental Methods For Investigating Charge Trapsmentioning
confidence: 99%
“…Tetracene surface undergoes a large structural relaxation, whereas the one of higher molecular weights rubrene 3 does not . Frisbie et al have recently reported that crystal step edges trap electrons on the surfaces of F2‐TCNQ 19 , Cl 2 ‐NDI 20 , and PDIF‐CN 2 21 . High‐resolution scanning Kelvin probe microscopy images combined with charge transport measurements show that the magnitude of the step edge potential is correlated with the sensitivity of µ to the number of step edges.…”
Section: Charge Transportmentioning
confidence: 99%